Normothermic Ex Vivo Heart Perfusion with Mesenchymal Stem Cell-Derived Conditioned Medium Improves Myocardial Tissue Protection in Rat Donation after Circulatory Death Hearts - Zifeng Zeng; Liwei Xu; Yu Xu; Yongsheng Ruan; Deshen Liu; Jiale Li; Chuanjie Niu; Shaoyi Zheng; Pengyu Zhou; Zezhou Xiao (Stem Cells International)
Objective. Adopting hearts from donation after circulatory death (DCD) is a promising approach to enlarge the donor pool. Nevertheless, DCD hearts experience severe warm ischemia/reperfusion (I/R) injury. Recent studies have demonstrated that conditioned medium (CM) derived from bone marrow mesenchymal stem cells (BMSCs) has the potential of reducing organ I/R injury. Therefore, we investigated whether DCD heart preservation with normothermic ex vivo heart perfusion (EVHP) and BMSCs-CM treatment could alleviate myocardial warm I/R injury in the DCD hearts. Methods. We randomly divided donor rats into two groups: (1) DCD-Control group and (2) DCD-CM group. Before DCD heart preservation with the normothermic EVHP system for 105 minutes, rats suffered from a 25-minute warm ischemia injury in the DCD procedure. Vehicle or CM (300 μl) was added to the perfusate at the beginning of the perfusion process. The cardiac function of DCD hearts in the DCD-Control and DCD-CM groups was measured every 30 minutes. Besides, non-DCD hearts were harvested from the beating-heart rats. Results. The antibody array demonstrated that the CM contained 14 bioactive factors involved in apoptosis, inflammation, and oxidative stress. Warm ischemia injury resulted in a significant increase in the level of oxidative stress, inflammation, and apoptosis in the DCD hearts of DCD-Control group. Furthermore, compared with the DCD-Control group, CM treatment increased the developed pressure, dP/dtmax and dP/dtmin of the left ventricular in the DCD hearts during a 90-minute EVHP. Moreover, the administration of CM attenuated the level of oxidative stress, inflammation, and apoptosis in the DCD hearts of the DCD-CM group. Conclusions. Normothermic EVHP combined with CM treatment can alleviate warm I/R injury in the DCD hearts by decreasing the level of oxidative stress, inflammatory response, and apoptosis, which might alleviate the shortage of donor hearts by adopting DCD hearts.